PHYSICOCHEMICAL CHARACTERIZATION OF PADDY SOILS CONTAMINATED WITH INDUSTRIAL WASTEWATERS: IMPLICATIONS FOR BIOREMEDIATION - Siti Khodijah Chaerun (Purifikasi, 2009)
Concern has mounted over recent decades regarding the paddy soils located in Rancaekek, Bandung, West Java, Indonesia that have been heavily polluted by industrial effluents for many years. Recent efforts to remediate the heavily polluted sites have failed due to incomplete understanding of the site characteristics. Hence, this study dealt with the physicochemical characterization of these soils to acquire a better understanding of the physicochemical impacts and eventually improve their soil quality so that they would again be suitable for agriculture. The polluted soils contained much higher salt concentrations, higher salinity, and elevated levels of heavy metals (Cr, Mn, Cu and Zn) than unpolluted soils at control sites. However, no significant difference was observed in the mean of pH between all sites. Maximum water holding capacity and cation exchange capacity (Na and K) in polluted soils were significantly greater than those in unpolluted soils. Moreover, the polluted soils had higher contents of N, P, K, S, organic C, and lower C/N ratio than unpolluted soils. These results indicate that the industrial wastewaters-contaminated paddy soils have major changes in their physicochemical characteristics, therefore being informative to the development of bioremediation strategies of these soils.